Abuse of Authority Against Judicial Power in Constitutional Court Decision No.90/PUU-XXI/2023 - Rismayani Rismayani; Dinda Difia Madina; Karimuddin Karimuddin (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Each law enforcer has its own authority according to what has been regulated in Indonesian laws and regulations. These provisions are stated in the Judicial Power Law No. 48 of 2009 which states that power judiciary according to The 1945 Constitution of the Republic of Indonesia is independent power . However, what has happened in Indonesia recently seems to be diminishing justice and putting aside codes of ethics in the world of law. The facts that occurred in the Constitutional Court decision No. 90 of 2023 regarding the age limit for presidential and vice presidential candidates were considered a decision that violated the code of ethics because there was a conflict of interest. In fact, the decision was built based on less than rational legal reasoning, resulting in a decision that was considered problematic. Based on the background description above, problems arise in the form of how a judge's authority should be in deciding cases in accordance with what is contained in the legislation. Then what are the legal remedies given in the form of sanctions to judges who are proven to be abusing their authority? This research uses a normative juridical approach, namely by looking at the rules and principles applied in the judiciary in Indonesia. The administration of government must be based on the principles of legality, protection, human rights and AUPB, especially in terms of the principle of not abusing power. Article 10 paragraph (1) letter e and the explanation of Law Number 30 of 2014 stipulate the principle of not abusing one's own authority. This basis requires every government agency and official not to exceed, abuse or confuse their authority for personal or other interests.